2009
DOI: 10.1158/1078-0432.ccr-08-2878
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Phosphatidylinositol-3′-kinase/AKT Signaling Is Essential in Hepatoblastoma Survival

Abstract: Purpose: Hepatoblastoma represents the most frequent malignant liver tumor in childhood. The phosphatidylinositol-3′-kinase (PI3K)/AKT pathway is crucial in downstream signaling of multiple receptor tyrosine kinases of pathogenic importance in hepatoblastoma. Increased PI3K/AKT signaling pathway activity and activating mutations of PIK3CA, encoding a PI3K catalytic subunit, have been reported in different childhood tumors. The current study was done to analyze the role of PI3K/AKT signaling in hepatoblastoma. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 28 publications
(35 reference statements)
1
46
1
1
Order By: Relevance
“…In addition, mutations were described in the PIK3CA gene, and in growth factors of this signaling pathway, such as IGF2, showing altered expression in this tumor type [59].…”
Section: Genetic Findings and Next-generation Sequencing Studiesmentioning
confidence: 99%
“…In addition, mutations were described in the PIK3CA gene, and in growth factors of this signaling pathway, such as IGF2, showing altered expression in this tumor type [59].…”
Section: Genetic Findings and Next-generation Sequencing Studiesmentioning
confidence: 99%
“…This pathway is often deregulated in cancer cells (45) as most of its proteins are tumor suppressor genes or proto-oncogenes whose mutation or anarchic expression can promote the development of a tumor (46,47).…”
Section: Pi3k/akt/mtor Axismentioning
confidence: 99%
“…It induces the activation of many intracellular proteins through cascades of phosphorylations (48). A study conducted by Hartmann et al (45) revealed that point mutation of the effector PI3KCA (p110α subunit of PI3K) was present in 2% of hepatoblastomas resulting in a gain of kinase activity. Moreover, they found that PI3K/AKT/mTOR activation was actually central for hepatoblastoma survival as demonstrated by PI3K inhibition in vitro and subsequent reduction of AKT and GSK3β phosphorylation (45).…”
Section: Pi3k/akt/mtor Axismentioning
confidence: 99%
“…For flow cytometric immunophenotyping, 3 Â 10 6 cells were fixed and stained using an Alexa Fluor 647 labeled phospho-(Ser10)-Histone H3 antibody (Cell Signaling Technology; 1:20) and a PE labeled cleaved-Poly(ADP-ribose)-polymerase (PARP; Asp214) antibody (BD Biosciences; 1:5) as well as DAPI (Sigma) to stain DNA as described. 22 FACS analyses were performed using a three-laser LSRII analytical flow cytometer (BD Biosciences, Heidelberg, Germany). Data were analyzed using Flowjo (Tree Star, OR) analysis software.…”
Section: Measurement Of Cellular Proliferation and Induction Of Apoptmentioning
confidence: 99%